Electrical evaluation of lighting lamps - Hernández-Corona, Jose Luis (2023)
The purpose of this research was to identify the harmonics caused by the pollution with non-linear loads such as energy-saving lamps and 10W LEDs. These lamps were compared with an incandescent lamp of the same power to establish the sinusoidal waveform. Electrical power, voltage, and current, as well as total harmonicdistortion percentages, were studied. These results were evaluated with the NI cRIO9023 controller for measuring power quality, and the NI-9225 voltage and NI-9227 current input modules. The visualization parameters were graphically and numerically displayed using ENA-Touch. The infrared spectrum was measured to determine the temperature of the power supply line and the neutral conductor. A harmonic attenuator filter, i.e., a second order high-pass RLC filter, was designed to mitigate the harmonic pollution. The results showed a decrease in the harmonic amplitude and the total harmonic distortion percentage.